Association between stress types and adolescent suicides: findings from the Korea Youth Risk Behavior Survey - Kim, Soo Young; Park, Yu Shin; Joo, Hye Jin; Park, Eun-Cheol (Frontiers in Psychiatry, 2024)
Objective: This study aims to explore the association between types of stress and suicidal behaviors-ideation and attempts-among Korean adolescents in two distinct years: 2015 and 2020.Methods: Data were acquired from the Korea Youth Risk Behavior Web-based Survey conducted in 2015 and 2020. Participants' desire for suicide was evaluated by asking questions about suicidal ideation and attempts, during the past year. Types of stress were divided into five categories: none, home, school, academic achievement, and appearance. Multiple logistic regression was used to investigate the association between variables of interest and dependent variables.Results: Among the 77,363 adolescents included in this study, 8.8% male and 13.2% female participants had seriously thought about committing suicide, and the rate of male and female participants who tried committing suicide was 1.6% and 2.5%, respectively. While every type of stress was highly associated with suicidal ideation, family and home types of stress had the highest odds ratio (OR), that was statistically significant for both sexes (Male: OR 3.81, 95% Confidence Interval [CI] 2.81 to 5.15; Female: OR 3.64, 95% CI 2.42 to 5.50). Moreover, the OR increased in order of: appearance; academic achievement; school and friends; and family and home, compared to the group that perceived no stress. Suicidal attempts were statistically significant and higher in likelihood, only amongst the female group that experienced stress from family and home (OR 2.48, 95% CI 1.08 to 5.67). In comparison to year 2015, suicidal ideation and attempts decreased in year 2020, but participants experiencing stress from family and home had a higher tendency of attempting suicide, though not statistically significant, regardless of their sex (Male: OR 1.03, 95% CI 0.74 to Running Title 2 1.44; Female: OR 1.06, 95% CI 0.81 to 1.4).